Cerebral Neovascularization in Diabetes: Implications for Stroke Recovery and beyond. Issue 4 (April 2014) - Ergul, Adviye; Abdelsaid, Mohammed; Fouda, Abdelrahman Y; Fagan, Susan C
Neovascularization is an innate physiologic response by which tissues respond to various stimuli through collateral remodeling (arteriogenesis) and new vessel formation from existing vessels (angiogenesis) or from endothelial progenitor cells (vasculogenesis). Diabetes has a major impact on the neovascularization process but the response varies between different organ systems. While excessive angiogenesis complicates diabetic retinopathy, impaired neovascularization contributes to coronary and peripheral complications of diabetes. How diabetes influences cerebral neovascularization remained unresolved until recently. Diabetes is also a major risk factor for stroke and poor recovery after stroke. In this review, we discuss the impact of diabetes, stroke, and diabetic stroke on cerebral neovascularization, explore potential mechanisms involved in diabetes-mediated neovascularization as well as the effects of the diabetic milieu on poststroke neovascularization and recovery, and finally discuss the clinical implications of these effects.